Mukjizat Dan Sihir: Analisis Pragmatik Dalam Kisah Para Rasul Serta Relevansinya Pada Konteks Kontemporer - Talifuddin, Fiona Isaura; Lintong, Aurel Chirstania Alexandra (Views : Jurnal Teologi dan Biblika, 2025)
Miracles and magic are two things whose meanings are often related in people's lives. Both lead to a miraculous act that sometimes people find it difficult to distinguish which miracles are from miracles and which are from magic. This study analyzes the two words in the context of the Acts of the Apostles and their relevance in the contemporary context. The research method used is qualitative research with a pragmatic linguistic approach to understand the meaning that arises from the context at that time. The results showed that the use of the word "miracle" in the text of Acts is a miraculous event centered on the transformation of faith and aims to glorify God. Whereas the word "magic" is used for miraculous events but for wrong or evil purposes, reflecting spiritual perversion and exploitation, and incompatible with the teachings of Christianity. In addition, this research seeks to provide a clear understanding in dealing with issues in the contemporary context, such as magical practices using Tarot cards conducted through social media and various practices of "smart people" and "shamans" in Indonesia. Based on the pragmatics of Acts, only God has power over the future and miracles are the result of the relationship between humans and God, not from various mystical tools or practices.